Writers at work / Dorothy E Zemach ; Lynn Stafford Yilmaz. - Zemach, Dorothy E.
This is the third book in a three-book series that provides students with a solid foundation in writing skills. The book adopts a process approach in which students use critical thinking and personal experience to compose well-structured and ac